2015
DOI: 10.1073/pnas.1512392112
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 somatic multiplex-mutagenesis for high-throughput functional cancer genomics in mice

Abstract: Here, we show CRISPR/Cas9-based targeted somatic multiplexmutagenesis and its application for high-throughput analysis of gene function in mice. Using hepatic single guide RNA (sgRNA) delivery, we targeted large gene sets to induce hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC). We observed Darwinian selection of target genes, which suppress tumorigenesis in the respective cellular/tissue context, such as Pten or Cdkn2a, and conversely found low frequency of Brca1/2 alterations, expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
150
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 49 publications
4
150
0
1
Order By: Relevance
“…A recent CRISPR validation study showed that gene Cdkn2a sgRNA and Ras oncogene overexpression, with sgRNAs targeting nine other tumor suppressor genes (TSGs) delivered by SB transposon, generated tumors, but only at 20-30 wk after injection (15). We performed tail vein injections to test whether Cdkn2a-sgRNA combined with oncogene NRAS G12V overexpression delivered by the PB vectors, pCRISPR-W9-Cdkn2a-sgRNA and pPB-hNRAS G12V (Fig.…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…A recent CRISPR validation study showed that gene Cdkn2a sgRNA and Ras oncogene overexpression, with sgRNAs targeting nine other tumor suppressor genes (TSGs) delivered by SB transposon, generated tumors, but only at 20-30 wk after injection (15). We performed tail vein injections to test whether Cdkn2a-sgRNA combined with oncogene NRAS G12V overexpression delivered by the PB vectors, pCRISPR-W9-Cdkn2a-sgRNA and pPB-hNRAS G12V (Fig.…”
Section: Significancementioning
confidence: 99%
“…However, because of their low efficiency, these two methods have not been widely used. Recently, CRISPR/Cas9 has been developed as an efficient mutagenesis tool (7)(8)(9) and was quickly adapted as a technique for in vivo tumor induction and validation of cancer genes (10)(11)(12)(13)(14)(15). By transplanting CRISPR librarytransduced cancer cells into immunocompromised mice, several genes involved in growth and metastasis of human lung cancer were identified (16).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Today, the CRISPR system has wide potential for applications in the field of cancer, including epigenetic cancer therapy [4], turning the genes involved in cancer development on and off, modelling cancer, examining the protein domains involved in cancer to evaluate the drug targets, reviewing and modelling the cancers in which several genes are involved or cancers that are caused by chromosomal clutter and rearrangements, and identifying the genes involved in cancer development [3,[43][44][45]. According to various genetic and epigenetic factors in cancer development, cancer modelling using the CRISPR system is expected play an important role in the detection and the identification of factors involved in cancer.…”
Section: Crispr and Cancermentioning
confidence: 99%